(untitled) (Jurnal Studi Inovasi Pemerintahan, 2025)
Introduction: Money politics is a crucial issue in Indonesian elections, including village legislative elections. The practice of giving rewards to influence voters undermines the integrity of democracy and the accountability of representation. This study aims to identify and analyze the practice of money politics in legislative elections in Lende Village, Sirenja District, Donggala Regency. By referring to Aspinall and Mada Sukmajati’s (2015) theory, this research examines forms of money politics such as vote buying, individual gifts, and club goods at the village level. Methods: This research uses a qualitative approach with a descriptive type. Data was collected through in-depth interviews with nine key informants including election organizers, election supervisors, village governments, successful teams of legislative candidates, and voters. In addition to interviews, secondary data was collected through documentation and observation to strengthen the analysis. Results: The results of this study show that the practice of money politics in Lende Village is manifested in three main manifestations. First, vote buying was carried out through the distribution of cash directly to community members. Second, individual gifts were also identified, in the form of providing basic necessities and various daily needs aimed at certain individuals and families. Third, the practice of money politics is also present in the form of the provision of club goods or facilities, such as the allocation of funding for village infrastructure development that can be utilized collectively by the entire community. Conclusion: The implications of these findings provide a deeper understanding to various related parties. For election organizers, the results of this study emphasize the urgency of more careful monitoring and effective law enforcement in an effort to eradicate the practice of money politics. Meanwhile, for candidates and political parties, this research is an important reflection on the quality of democracy and the legitimacy of people’s representatives. Furthermore, for the public as voters, it is hoped that the results of this research can raise awareness of the potential dangers of money politics and encourage more rational and integrity-based voter participation.